Topologically Porous Heterostructures for Photo/Photothermal Catalysis of Clean Energy Conversion. Issue 4 (22nd February 2023) - Gao, Fan; Wang, Xinqiang; Cui, Wen‐Gang; Liu, Yanxia; Yang, Yaxiong; Sun, Wenping; Chen, Jian; Liu, Ping; Pan, Hongge
Abstract: As a straightforward way to fix solar energy, photo/photothermal catalysis with semiconductor provides a promising way to settle the energy shortage and environmental crisis in many fields, especially in clean energy conversion. Topologically porous heterostructures (TPHs), featured with well‐defined pores and mainly composed by the derivatives of some precursors with specific morphology, are a major part of hierarchical materials in photo/photothermal catalysis and provide a versatile platform to construct efficient photocatalysts for their enhanced light absorption, accelerated charges transfer, improved stability, and promoted mass transportation. Therefore, a comprehensive and timely review on the advantages and recent applications of the TPHs is of great importance to forecast the potential applications and research trend in the future. This review initially demonstrates the advantages of TPHs in photo/photothermal catalysis. Then the universal classifications and design strategies of TPHs are emphasized. Besides, the applications and mechanisms of photo/photothermal catalysis in hydrogen evolution from water splitting and CO x hydrogenation over TPHs are carefully reviewed and highlighted. Finally, the challenges and perspectives of TPHs in photo/photothermal catalysis are also critically discussed. Abstract : In this review, the design categories of topologically porous heterostructure are systematically highlighted. The recent progress of their photo/photothermal catalysis applications, including photocatalytic hydrogen generation from water splitting, photoreduction of CO2, photothermal CO x hydrogenation are also comprehensively presented.